A Comprehensive Review on Amoxicilin and Clavulanic Acid as Potential Antibacterial Agent - Jeet, Kamal; Kumar, Sanjay; Singh, Gajender; Jaswal, Rajat; Kumar, Dikshit; Thakur, Amit (Asian Journal of Pharmaceutical Research and Development, 2022)
Suspensions comprise finely divided medication particles (the suspensoid) spread uniformly in a vehicle with or without stabilisers and other ingredients. Conventional oral suspension is ready-to-use and does not require reconstitution. Dry syrup is more bioavailable than tablets and capsules because it dissolves in water outside the mouth and enters the GI tract. GIT absorbs suspension quickly: Amoxicillin and clavulanic acid have been used since the 1970s. Despite having the same half-life as amoxicillin, clavulanic acid is protein-bound and heat unstable. It causes gastrointestinal side effects, including Clostridium difficile infection, and restricts amoxicillin oral combination doses. Due to clavulanic acid’s b-lactamase tendency, the first amoxicillineclavulanic acid ratio was 4:1; currently it’s 2:1, 7:1, 14:1, and 16:1. Few ratio comparisons exist. Amoxicillineclavulanic acid is often used as empiric therapy for WHO’s Priority Infectious Syndromes in adults and children, resulting in large consumption. Some of these syndromes may be handled with a delayed antibiotic prescription approach or amoxicillin alone.